Intermediated technology use in developing communities - Sambasivan, Nithya; Cutrell, Ed; Toyama, Kentaro; Nardi, Bonnie (CHI '10: Proceedings of the 28th international conference on Human factors in computing systems, 2010)
We describe a prevalent mode of information access in low-income communities of the developing world—intermediated interactions. They enable persons for whom technology is inaccessible due to non-literacy, lack of technology-operation skills, or financial constraints, to benefit from technologies through digitally skilled users—thus, expanding the reach of technologies. Reporting the results of our ethnography in two urban slums of Bangalore, India, we present three distinct intermediated interactions: inputting intent into the device in proximate enabling, interpretation of device output in proximate translation, and both input of intent and interpretation of output in surrogate usage. We present some requirements and challenges in interface design of these interactions and explain how they are different from direct interactions. We then explain the broader effects of these interactions on low-income communities, and present some implications for design.
Best of CHI honorable mention